Analysis of Factors Affecting Regional Original Revenue (PAD) Disparities among Provinces on Java Island - Kusumawardani, Agustina Putri Dwi; Asmara, Kiky (Journal of Regional Economics and Development, 2026)
This study analyzes the factors influencing disparities in Regional Own-Source Revenue (PAD) across provinces in Java Island for the period 2013–2024. Independent variables include Gross Regional Domestic Product (GRDP), Labor Force Participation Rate (LFPR), and population size. Using a panel data regression approach with the Fixed Effect Model (FEM), the study finds that GRDP and LFPR have a significant positive effect on PAD, while population size shows no significant impact. These findings highlight the crucial role of economic growth and active workforce participation in strengthening local fiscal capacity. Furthermore, revenue disparities arise due to differences in economic productivity, industrial structure, and workforce quality across provinces.